The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1136/archdischild-2019-316929
|View full text |Cite
|
Sign up to set email alerts
|

The First Thousand Days: early, integrated and evidence-based approaches to improving child health: coming to a population near you?

Abstract: The ‘First Thousand Days’ refers to the period from conception to the child’s second birthday. It is increasingly gaining traction as a concept to guide public health policy. It is seen as a crucial window of opportunity for interventions that improve child and population health. This review outlines the origin and growth of the First Thousand Days concept, and the evidence behind it, particularly in the areas of brain development and cognition; mental and emotional health; nutrition and obesity; programming a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 20 publications
0
38
0
6
Order By: Relevance
“…14 Specifically, a review suggested that early life circumstances are fundamental for good health in adulthood. 15 The period of "The First Thousand Days" of life (ie, the period from conception to the child's second birthday) is considered to provide a window of opportunity for early support of healthy growth and development of children. [16][17][18] This is in line with findings from Lee et al, 10 who suggested that poverty before age 2 was associated with the development of obesity in adolescence.…”
mentioning
confidence: 99%
“…14 Specifically, a review suggested that early life circumstances are fundamental for good health in adulthood. 15 The period of "The First Thousand Days" of life (ie, the period from conception to the child's second birthday) is considered to provide a window of opportunity for early support of healthy growth and development of children. [16][17][18] This is in line with findings from Lee et al, 10 who suggested that poverty before age 2 was associated with the development of obesity in adolescence.…”
mentioning
confidence: 99%
“…It refers to the period from conception to the child’s second birthday and is increasingly gaining traction as a concept for guiding public health policy. It is widely recognized as a crucial window of opportunity for interventions that improve child and population health [ 39 ]. In recent years, Gasbarrini et al have concentrated much effort on studying gut microbiota formation, establishment, and possibility of modulation in health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…As evidence increasingly highlights the importance of nutrition through the critical stages of development in the first 1000 days (Darling et al 2020 Two striking gaps in the methods for developing infant feeding guidelines were identified in this report: the lack of use of systematic review methodology and the infrequent use of a harmonized approach to setting guidelines across agencies or societies either within a country or across countries. The opportunity exists for Canada to build on the excellent foundation established by Health Canada and partner organizations to update the infant feeding recommendations of 2014-15 (Health Canada et al 2014;Health Canada et al 2015) and to expand them to include pre-conception, pregnancy and lactation.…”
Section: Take Home Messages For Canadamentioning
confidence: 98%